Pulse plated silver metallization on porosified LTCC substrates for high frequency applications. (May 2016) - Steinhäußer, Frank; Talai, Armin; Sandulache, Gabriela; Weigel, Robert; Koelpin, Alexander; Hansal, Wolfgang; Bittner, Achim; Schmid, Ulrich
Abstract: Advanced high frequency systems such as needed in modern radar applications, require high conductive metallizations as well as substrates with areas of variable permittivity. This paper presents the combination of the selective porosification technology of low temperature co-fired ceramics (LTCC) and electro pulse plated silver microstrip lines. By means of selective plating methods, line widths of 20 μm can be manufactured featuring low resistivity values down to 2.33 μΩ cm, without detectable pore penetration. The substrate permittivity is measured facilitating a combined method of ring resonator detuning and 3D field simulations resulting in a reduction of 6.5% with a shift from approx. 7.52 to 7.03 at 66 GHz due to the porosification. As often outlined in literature, the major challenge in using silver as a conductor lies in its high tendency of agglomeration and microstructural transformation especially in oxygen containing atmosphere even at low temperatures. Therefore, the effect of different temperature loads up to 500 °C on the dc film resistivity is measured using the van der Pauw technique and is compared to scanning electron microscope analyses.